(untitled) (Progressive Agriculture, 2017)
Productivity of the cropping system is critical to the food security of Bangladesh. However, many concerns about the sustainability of cropping system exist because of lack of advance knowledge of farming. In this context, a study was performed in the agro-ecological zone of the Tista Mendar Floodplain agro ecological zone (AEZ-3) at Jaldhaka subdistrict under Nilphamary district of Bangladesh. By reorganization of existing cropping patterns (using Linear Programming Model) gross output (7% to 21%), gross margin (12% to 20%) and labour employment (6% to 20%)have been increased from plan1(existing plan) to plan2 (by reorganization of existing lands). The cause of increase gross output, gross margin andlabour employment was some cultivated land from less efficient cropping patterns has been transferred to more efficient cropping patterns. Again, by reorganization of existing and improved cropping patterns, some lands of existing patterns have been shifted to improved cropping pattern. As a result, gross out (17% to 31%), gross margin (27% to 32%) and labour employment (13% to 26%) have been raised from plan1 to plan 3 (by combination of improved technologies with existing technologies). The result of on farm demonstration showed gross output, gross margin and labour employment have been increased 24% to 53%, 32% to 51% and 12% to 47% from plan1 to plan 3, respectively. So, this study suggest, optimum farm plan with the combination of existing and improved cropping pattern will increase farm output and generate additional employment and improved food security. Progressive Agriculture 28 (3): 204-215, 2017